A Critical Discourse Analysis of Ideology in Selected Iraqi Memes on Facebook - Amer Sagheer Allwan Al Amery (Randwick International of Education and Linguistics Science Journal, 2023)
Nowadays, people tend to use various ways of communication to communicate, deliver messages, express ideas and opinions and/or influence others. Due to the advancement of technology in general and social media in particular, using memes is considered one of easiest and most influential ways of spreading opinions that carry overt and covert ideologies. This study is aimed to reveal how Iraqi internet users employ these internet memes to spread their ideologies. The study takes into consideration the semiotic, linguistic and socio-cultural dimensions into consideration in analyzing the visual-textual aspects of these selected Iraqi memes to reach a better understanding of the purpose and the profound meanings of such memes that people might not fully grasp. The researcher tries critically, by using Fairclough (1989) and Wodak (2011) approaches, analysing the overt and covert ideologies implied in the language of internet memes and show how these ideologies can be used to affect others within its social-cultural context.